Beyond information seeking: Consumers' online deliberation about the risks and benefits of red meat. (January 2015) - Rutsaert, Pieter; Barnett, Julie; Gaspar, Rui; Marcu, Afrodita; Pieniak, Zuzanna; Seibt, Beate; Lima, Maria Luisa; Fletcher, Dave; Verbeke, Wim
Highlights: A measure of online deliberation about red meat risks and benefits is validated. Questions asked, comments given, links clicked, time spent compose the measure. Perceiving information about red meat as too complex decreases deliberation. Deliberation increases information recall about red meat risks and benefits. Abstract: Successfully engaging consumers in a dialogue may provide opportunities for better tailored and more effective communication about food-related risks and benefits. Using an online deliberation concept and software, VIZZATA™, we explored the validity of a behavioral measure of deliberation in an online environment in the context of consumers' perceptions and information seeking about the risks and benefits of red meat. Participants from Belgium, Portugal and the United Kingdom ( n  = 150) were given the opportunity to engage in an asynchronous interaction with the research team about the information provided. Online deliberation was operationalized as an individual metric based on the number of questions asked in relation to the information, the number of comments left, the number of glossary terms accessed, and the time spent on deliberative activity. This operationalization provided a coherent measure of deliberation which was positively correlated with information recall about the risks and benefits of red meat. Participants who perceived the information about red meat risks and benefits as too complex engaged less with the information. The study herewith presents a novel method of investigating consumers' deliberation about food issues that conceptualizes consumer engagement as more than just information seeking.